MEMBEDAH SKEMA STRUKTURASI PRAKTIK PORNOGRAFI DI INDONESIA - Imadah Thoyyibah; Rahmad Alamsyah (LPPM STISIP Persada Bunda, 2022)
This study aims to dissect the structuration pattern between agents and structures in the structural dimension behind the practice of pornography in Indonesia. The analysis is descriptive qualitative with data collection techniques using library data sources and empirical data from various media sources that have been factually documented. Structuring is the stretching or structuring of social relations across space and time based on the principle of duality relations, which means there is a reciprocal relationship and interrelationship between structure and agent. Based on the structuration scheme, the practice of pornography involves three dimensions of structure; namely signification (signification), domination (mastery), and legitimacy (justification) which are interrelated. The three dimensions of the structure that are both a means and a resource for the practice of pornography include; 1) the pattern of marking and meaning of pornographic material; 2) the pattern of global domination and authority of the capitalist economy industry; and 3) patterns of legitimacy and the mobilization of sanctions through cultural norms, artistic ideology, and freedom of expression. Structurally, the agent collaborates with the abstract system/expert system to regularize pornographic material into public consumption on a regular basis, creating practical awareness for the agents. This regularization is reproduced in people's behavior along with culture, discourse on sexuality, art and freedom of expression.